1992
DOI: 10.1002/jbt.2570070302
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the active transport of serotonin into mouse platelets by the sulfhydryl oxidizing agent diamide

Abstract: The purpose of this study was to determine the effects of diamide, a reversible sulfhydryl oxidizing agent, on the transport of serotonin (5-HT) by mouse platelets. Diamide produced a concentration-dependent (10-200 microM) stimulation of 5-HT transport that was rapid and sustained over 0-10 minutes of incubation. When platelets were incubated with diamide (10-200 microM) in the presence of glucose, the content of reduced glutathione was significantly decreased only at a final concentration of 200 microM, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that disulfides are critical determinants of serotonin transporter function. Disulfide oxidation has been reported to stimulate serotonin transport in mouse platelets [17], whereas reduction increases the affinity for imipramine, a potent serotonin uptake inhibitor [18]. These observations may indicate that the binding affinity of SERT1 is altered upon oligomerization.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that disulfides are critical determinants of serotonin transporter function. Disulfide oxidation has been reported to stimulate serotonin transport in mouse platelets [17], whereas reduction increases the affinity for imipramine, a potent serotonin uptake inhibitor [18]. These observations may indicate that the binding affinity of SERT1 is altered upon oligomerization.…”
Section: Discussionmentioning
confidence: 96%
“…A key gene significantly differentially Genes differentially expressed in tph+ neurons of lhx1/5-1(RNAi) animals were enriched in GO terms related to tryptophan metabolic process, response to diamide and presynaptic organisation (Figure 4B, Supplementary File 8). Notably, there is evidence concerning the influence of diamide, a sulfhydryl oxidising agent, on serotonin (5-HT) transport [55]. In particular, diamide simulates 5-HT transport in a concentration-dependent manner, with fluoxetine -a selective inhibitor of serotonin reuptake -constraining this effect [55].…”
Section: Effects Of Serotonergic Transcription Factor Gene Knockdown ...mentioning
confidence: 99%
“…Notably, there is evidence concerning the influence of diamide, a sulfhydryl oxidising agent, on serotonin (5-HT) transport [55]. In particular, diamide simulates 5-HT transport in a concentration-dependent manner, with fluoxetine – a selective inhibitor of serotonin reuptake – constraining this effect [55]. A key gene significantly differentially regulated in this analysis was the serotonin synthesis rate-limiting enzyme tph (h1SMcG0000075, Supplementary File 7).…”
Section: Introductionmentioning
confidence: 99%